ATSAR ITBAA' MADKHAL AL-TA'ALLUM AL-TA'AWUNIY FII TA'LIIM AL-NAHW - Abdillah, Rifki; Maswani, Maswani (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
The objective of this study is to get empirical evidence whether is a significant difference score for the class which is taught by applying cooperative learning study in studying nahw. This study categorized as an experimental study in quantitative research. Experimental class is taught by applying cooperative learning while the control class is taught by using conventional method. The data is collected by giving test for experimental class and control class. The result at the study shows that experimental class which is taught by applying cooperative learning get higher score 82,2. Therefore the conventional class gat lower score 74,1. It seems that studying nahw by applying cooperative learning is effective.DOI: 10.15408/a.v2i1.1518